Plastic surgery for breast cancer: еssentials, classification, performance algorithm - A. Kh. Ismagilov; A. S. Vanesyan; A. R. Khamitov; I. F. Kamaletdinov (Опухоли женской репродуктивной системы, 2015)
The choice of plastic surgical techniques for cancer is influenced by two factors: resection volume/baseline breast volume ratio and tumor site.Based on these factors, the authors propose a two-level classification and an algorithm for performing the most optimal plastic operation onthe breast for its cancer.